Let's tweet again? The impact of social networks on literature achievement in high school students : Evidence from a randomized controlled trial - Gian Paolo Barbetta; Paolo Canino; Stefano Cima (Università Cattolica del Sacro Cuore, Dipartimento di Economia e Finanza (DISCE), 2019)
The availability of cheap wi-fi internet connections has stimulated schools to adopt Web 2.0 platforms for teaching. Using social networks and micro-blogs, teachers aim to stimulate students' participation in school activities and their achievement. Although anecdotal evidence shows a high level of teacher satisfaction with these platforms, only a small number of studies has produced rigorous estimates of their effects on students' achievement. We contribute to the knowledge in this field by analyzing the impact of using micro-blogs as a teaching tool on the reading and comprehension skills of students. Thanks to a large-scale randomized controlled trial, we find that using Twitter to teach literature has an overall negative effect on students' average achievement, reducing performance on a standardized test score by about 25 to 40% of a standard deviation. The negative effect is heterogeneous with respect to some students' characteristics. More specifically, the use of this Web 2.0 application appears to have a stronger detrimental effect on students who usually perform better.
Keywords: I21; 330; ICT; education; literature performance; RCT